Preliminary reflections on the failure of the Brumadinho tailings dam in January 2019. Issue 3 (6th August 2019) - Cambridge, Mike; Shaw, Darren
Abstract : The failure on 25 January 2019 of the Brumadinho dam 1 at the Minas Córrego do Feijão in the Minas Gerais region of Brazil resulted in at least 220 deaths, together with major environmental impacts on the downstream catchment. This was the fifth tailings dam disaster to have occurred in the same region in an 18 year period. An international investigation was subsequently initiated and a large volume of information has since been circulated, much of it on the Internet, and much of it contradictory. This paper summarises what is known of the event and explores the regional, historical and regulatory context of the disaster. Based on the limited information available, the incident is put into a geotechnical context with regard to the application of upstream construction methods to this facility and other sites in Minas Gerais and a brief review of the history of the design, construction and operation to this facility is presented. Without pre-judging the outcome of the official enquiry, a preliminary assessment of the possible causes of the failure is explored and the implications for future tailings dam construction, particularly by the upstream method, assessed.